Kontribusi Fatayat NU Dalam Mendukung Pelaku UMKM Di Kabupaten Tulang Bawang Barat ( Studi Kasus: Penjual Busana Muslimah - Novia Dwi Arini; Didik Kusno Aji Nugroho; Muhammad Agus Mushodiq; Subandi; Ahmad Muslimin (Bulletin of Community Engagement, 2025)
Fatayat NU, a women's organization under the umbrella of Nahdlatul Ulama, plays a strategic role in community empowerment, particularly in promoting Islamic economics and Sharia-compliant lifestyles. In Tulang Bawang Barat Regency, however, understanding of Muslim women’s clothing in accordance with Sharia principles remains limited. This is attributed to a lack of structured education, cultural constraints, and restricted access to relevant information. Despite these challenges, adherence to a Sharia-compliant lifestyle is increasing in tandem with growing religious awareness. Within this context, Fatayat NU’s 2019–2024 leadership is expected to act as an agent of change by advancing small and medium enterprises (SMEs) in the Muslim fashion sector. This study adopts a qualitative approach, employing observation, interviews, and documentation methods. Data were collected through in-depth interviews with Fatayat NU administrators who had received training in Islamic economics and Muslim fashion design. The findings reveal that Fatayat NU contributes significantly to the development of Muslim fashion-related MSMEs by organizing training workshops on fashion graphic design and seminars on Islamic economic principles, including sales bookkeeping practices. These efforts have supported increased sales in stores operated by Fatayat NU members who participated in the programs. The success of these initiatives demonstrates that Fatayat NU can serve as a model for community empowerment by integrating Islamic values with practical economic solutions. Nonetheless, the organization continues to face challenges, including limited funding, cultural resistance, and insufficient external support.